Performance Analysis of Cutting Glass Fibre Epoxy Reinforced Composites Using an Abrasive Water Jet Machining Process - Wan Abdul Rahaman, Wan Emri; Tharazi, Izdihar; Sarizam, Muhamad Iltizam Ezwan (International Journal of Integrated Engineering, 2024)
Abrasive Waterjet Machining (AWJM) is a versatile cutting process that involves directing a high-velocity stream of water mixed with abrasive particles to remove material and create holes and cavities in solid materials. In this study, the impact of abrasives waterjet machining (AWJM) parameters, including traverse speed, stand-off distance, and abrasive flow rate, while maintaining a constant pressure, on glass fiber epoxy composites were investigated. The glass fiber composites were made up of 50% glass fiber, 47% epoxy, and 3% graphite by weight. The aim of this study is to assist industries and individuals in selecting optimal AWJM parameters to achieve desired kerf width and surface roughness while meeting specified standards. Central Composite Design (CCD) integrated with Responsive Surface Methodology (RSM) was employed to determine the experimental parameters. Analysis of Variance (ANOVA) and regression models were established to predict kerf width and surface roughness based on primary and interaction effects of process parameters. Kerf width was measured using a vernier caliper, while surface roughness was assessed using a surf test machine (SV-600). The study reveals that surface roughness is influenced by machining parameters such as stand-off distance, traverse speed, and abrasive flow rate, along with the interaction between stand-off distance and traverse speed. In contrast, kerf width is predominantly influenced by stand-off distance and traverse speed. Additionally, a morphological analysis of the samples was conducted using Optical Microscopy and Scanning Electron Microscopy (SEM) to examine surface microstructures.